Poland’s Economic Problems during the War with the Bolsheviks – Overview - Podolska-Meducka, Aldona (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The article identifies the main economic problems Poland faced as a result of its military involvement in the 1919–1921 Polish-Soviet War. Research Design & Methods: Source material including legal regulations, statistical data and pre- and post-war literature were analysed. Findings: Financing military operations replete with supplies took a tremendous effort, and the consequent hardship was shouldered by all of Poland’s citizens. The situation weighed particularly heavily on rural populations, which were compelled to provide recruits and food for the army and civilians alike. The war ultimately ushered in a period of hyperinflation. Implications / Recommendations: War places a huge burden on state finances. It contributes to a greater state interventionism and imposes various obligations on the citizens. Contribution: The analysis of main problems of Polish economy during the Polish-Soviet War may be used for comparative purposes when studying similar issues in other countries.